Cell‐Penetrating, Dimeric α‐Helical Peptides: Nanomolar Inhibitors of HIV‐1 Transcription1. Issue 38 (23rd July 2014) - Jang, Sangmok; Hyun, Soonsil; Kim, Seoyeon; Lee, Seonju; Lee, Im‐Soon; Baba, Masanori; Lee, Yan; Yu, Jaehoon
Abstract We constructed dimeric α‐helical peptide bundles based on leucine (L) and lysine (K) residues for both efficient cell penetration and inhibition of the Tat–TAR interaction. The LK dimers can penetrate nearly quantitatively into eukaryotic cells and effectively inhibit the elongation of the TAR transcript at low nanomolar concentrations. The effective inhibition of HIV‐1 replication strongly suggests that the LK dimer has strong potential as an anti‐HIV‐1 drug.